2011
DOI: 10.1089/thy.2011.0029
|View full text |Cite
|
Sign up to set email alerts
|

Levothyroxine Replacement Doses Are Affected by Gender and Weight, But Not Age

Abstract: Background: Body weight (BW) and age have been shown to affect the dose of levothyroxine (LT 4 ) that results in normalization of serum thyroid-stimulating hormone (TSH) in hypothyroid patients. Our objective was to determine whether gender, menstrual status, and ideal BW (IBW) also affect the LT 4 dose required to achieve a serum TSH within the normal range. Methods: We retrospectively reviewed the charts of patients being treated for primary hypothyroidism who had TSH values within a normal range. We select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 36 publications
3
48
0
7
Order By: Relevance
“…On the other hand, Franklyn et al suggested that increasing age alone does not significantly influence thyroid hormone measurements [12]. A more recent study also suggested that age does not directly affect FT4 replacement requirements, and age-based differences in doses are secondary to differences in body weight and gender [13]. These findings correlate to the results of our categorical analyses.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…On the other hand, Franklyn et al suggested that increasing age alone does not significantly influence thyroid hormone measurements [12]. A more recent study also suggested that age does not directly affect FT4 replacement requirements, and age-based differences in doses are secondary to differences in body weight and gender [13]. These findings correlate to the results of our categorical analyses.…”
Section: Discussionsupporting
confidence: 87%
“…The data presented above explain the findings of previous studies (13) in which doses of levothyroxine needed for patients in menopause were smaller (1.49 μg/kg/day) than those of premenopausal patients (1.51 μg/kg/day). In our study, considering women under and over 50 years old, the dose was higher for the younger patients (< 50 years), but the difference was not statistically significant.…”
Section: Discussionsupporting
confidence: 82%
“…Initial recommended daily dose for clinical hypothyroidism in < 60 years old patients is 1.6-1.8 μg/ kg ideal body weight (190) (B). No differences were found between slow or full starting dose (191) …”
Section: How Should Levothyroxine Be Used?mentioning
confidence: 99%
“…Two studies by Jonklaas et al [26] and Devdhar et al [27] suggest that the levothyroxine dose required by pre-and postmenopausal women disappear are the same if they are assessed using ideal weight, rather than using current body weight. These authors attributed the alterations that occur during aging to the change in weight.…”
Section: Discussionmentioning
confidence: 99%